porfavor me ajudem preciso disso pra amanhã !!

Resposta:
Explicação passo a passo:
[tex]a)[/tex]
[tex]3^{9} .9^{-2} =3^{9}.(3^{2})^{-2} =3^{9}.3^{-4} =3^{(9-4)} =3^{5}[/tex]
[tex]27^{7} .81^{-5} =(3^{3} )^{7} .(3^{4}) ^{-5} =3^{21} .3^{-20} =3^{(21-20)} =3^{1}=3[/tex]
Portanto...
[tex]\frac{3^{5} }{3} =3^{(5-1)} =3^{4} =81[/tex]
[tex]b)[/tex]
[tex](2^{-4}) ^{2}.(2^{-2}) ^{3} =2^{-8} .2^{-6} =2^{(-8-6)} =2^{-14}[/tex]
[tex]2^{-3} .2^{-11} =2^{(-3-11)} =2^{-14}[/tex]
Portanto...
[tex]\frac{2^{-14} }{2^{-14} } =1[/tex]